RATE OF CONCERT CHEMICAL REACTION AT LOW TEMPERATURES - E. S. Bragina; E. S. Savin (Тонкие химические технологии, 2013)
In adiabatic approach the assessment of rate of direct and synchronous transitions of nuclear kernels between various provisions of balance is made at low temperatures. Conditions of efficiency of concert transitions in comparison with direct transitions are received.